The Director Within : Storytellers of Stage and Screen - Eichenbaum, Rose; Eichenbaum, Rose (Book collections on Project MUSE., 2014)
In Rose Eichenbaum's latest book on the confluence of art making and human expression, she sits down with thirty-five modern day storytellers-the directors of theater, film, and television. Eichenbaum's subjects speak with revealing clarity about the entertainment industry, the role and life of the director, and how theatrical and cinematic storytelling impacts our culture and our lives. The Director Within includes interviews with Peter Bogdanovich (The Last Picture Show), Julie Taymor (The Lion King), Mel Brooks (Blazing Saddles), Tim Van Patten (The Sopranos, Boardwalk Empire), Hal Prince).